THE HISTORY OF THE URBAN PLANNING CULTURE OF UZBEKISTAN AND THE ROLE OF THE AFROSIAB MONUMENT IN ITS STUDY - Aliqulov, Begzod (Science technology&Digital finance, 2023)
The article tells about the emergence, development of urban planning in Uzbekistan, thoughts about the Afrosib monument.